Growing evidence of pharmacotherapy effectiveness in managing attention-deficit/hyperactivity disorder in young children with or without autism spectrum disorder: a minireview - Alsayouf, Hamza A. (Frontiers in Psychiatry, 2024)
Many children with autism spectrum disorder (ASD) also have attention deficit/hyperactivity disorder (ADHD). ADHD in children is associated with increased risk of negative outcomes, and early intervention is critical. Current guidelines recommend psychosocial interventions such as behavioral training as the first line of therapy in managing ADHD symptoms in children with or without ASD. Where symptoms are refractory to these interventions, medications such as stimulants, α2-adrenergic agonist inhibitors, selective norepinephrine reuptake inhibitors, and second-generation antipsychotics are recommended. However, these pharmacotherapies do not have regulatory approval for use in children of preschool age, and evidence on their safety and efficacy in this population has historically been very limited. Since publication of the current guidelines in 2020, several new randomized controlled trials and realworld studies have been published that have investigated the efficacy and tolerability of these medications in preschool children with ADHD, with or without comorbid ASD. Here, we provide a review of the key findings of these studies, which suggest that there is growing evidence to support the use of pharmacological interventions in the management of ADHD in preschool children with comorbid ASD.